DAMPAK MEDIA SOSIAL TIKTOK DALAM PERILAKU MORAL SISWA KELAS V SEKOLAH DASAR NEGERI 011 SAMARINDA KOTA TAHUN PEMBELAJARAN 2024/2025 - Dwi Wulan Fitriani; Taufik Hidayat; Yudo Dwiyono, Tri Wahyuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the impact of TikTok social media use on the moral behavior of fifth-grade students at SD Negeri 011 Samarinda Kota in the 2024/2025 academic year. The background of this research arises from the growing phenomenon of TikTok usage among elementary school students, which potentially brings both positive and negative effects on moral development. This research employed a descriptive qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation of techniques, triangulation of sources, and member checking. The findings indicate that TikTok has negative impacts, such as decreased politeness, the use of slang or viral expressions, learning disruptions, reduced concentration, and signs of addiction that affect students’ social interactions and academic performance. On the other hand, TikTok also provides positive contributions, such as enhancing students’ creativity in producing video content, serving as entertainment, and providing new information and insights. The role of teachers and parents is crucial in minimizing negative impacts by supervising and promoting digital literacy practices. Based on this study, the indication of TikTok addiction points to a moderate level within a serious warning zone. This is evident from the shift in students' moral behavior, where their speech patterns changed to more frequent use of viral slang and less polite or rude language. Furthermore, usage duration exceeds 2 hours per day, and students' concentration decreases, sometimes leading them to neglect mandatory school assignments given by teachers. This study concludes that TikTok is a double-edged phenomenon that must be managed wisely to maximize its benefits while reducing its risks. Future research is recommended to expand the scope of variables and contexts to provide a more comprehensive